Does the Fukushima nuclear accident still matter? Analysis of its mediated effects on five dimensions of nuclear power acceptance by using the parallel multiple mediator model - Kim, Geunsik; Kim, Seoyong (Energy Strategy Reviews, 2023)
Although 10 years have passed since the Fukushima nuclear accident, it continues to greatly impact global energy policy and the acceptance of nuclear power. This study aims to empirically analyze the Fukushima accident's effects on five dimensions of nuclear power acceptance and the interactions of these effects with various determinants of nuclear power acceptance. We analyze survey data from 1020 Korean respondents and find that they remain highly worried about the Fukushima accident 10 years later. The Fukushima accident has negative impacts on the general acceptance of nuclear power, acceptance of nuclear power's contributions to addressing climate change, acceptance of high-level radioactive waste disposal sites, and acceptance of extensions of old nuclear power plants. However, the accident has a positive impact on the acceptance of denuclearization policies. Our parallel multiple mediator model shows that the Fukushima accident has only an indirect effect on general acceptance; this effect is negative and significant. The accident has a positive direct and indirect effect on acceptance of denuclearization policies but negative direct and indirect effects on the acceptability of high-level nuclear waste disposal and extensions of old nuclear power plants. Finally, we find a positive direct effect and a negative indirect effect of the accident on acceptance of nuclear power's contributions to addressing climate change. The latter is greater than the former, meaning that acceptance of nuclear power in the context of addressing climate change fell in response to the accident. In short, the Fukushima accident has different direct and indirect effects across different dimensions of nuclear power acceptance.
Keywords: Fukushima accidents; Fukushima nuclear accidents; Fukushimum accident effect; Global energy; Indirect effects; Mediator modeling; Multidimensional acceptance of nuclear power; Parallel multiple mediator model; Public acceptance; Public acceptance of nuclear power; Fukushima accident effect; Multidimensional acceptance of nuclear power; Parallel multiple mediator model; Public acceptance of nuclear power